Akar Kebudayaan Barat - Hamid Fahmy Zarkasyi (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2013)
In  tracking  down  the  cultural  history  owned  by  civilliation,  it  is  important  to conduct research based on worldview perspective. Because every society scientifi activity will create their own worldview. The wordview that built above these scientific elements will construct their cultures.  Worldview is certainly may  not formed by it self. It will match, get acquinted, and assimilated with worldviews of many other civilizations.This theory  approved  by  many  scholars  as  structure  determined  birth  of  cultures  of  any civilizations, including the West. West culture on its birth and development also relies on  Western  Worldview.  Western  Worldview  turned  out  in  their  history  related  very intense with Islamic Worldview which manifestated in the constructs of civilization that also covers therein culture concepts. Islamic Worldview gives a great influence on construct of Western Worldview.Including concepts of Western culture.